2017
DOI: 10.17161/foec.v41i2.6835
|View full text |Cite
|
Sign up to set email alerts
|

Science and Social Studies for Students With Disabilities

Abstract: Science and social studies have much to offer to all learners-including those with disabilities. However, instruction in these subjects has often been overlooked in the quest to better understand and improve leaning in English/language arts and mathematics. As we demonstrate in this paper; science and social studies help students attain skills, information, and dispositions that are important for success in school and everyday life. Furthermore, these subjects offer opportunities for students to learn and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Thus, it is important to teach vocabulary explicitly and systematically, using effective strategies to support students in developing their academic vocabulary (Beach, Sanchez, Flynn, & O'Connor, ). What follows are some examples of effective practices for teaching vocabulary to struggling students suggested by previous studies (Scruggs & Mastropieri, ; Scruggs et al., ). Students acquire academic vocabulary easily when student‐friendly definitions (i.e., using grade‐level‐appropriate vocabulary) are used rather than dictionary definitions (Beck et al., ).…”
Section: Effective Vocabulary Instruction In Social Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Thus, it is important to teach vocabulary explicitly and systematically, using effective strategies to support students in developing their academic vocabulary (Beach, Sanchez, Flynn, & O'Connor, ). What follows are some examples of effective practices for teaching vocabulary to struggling students suggested by previous studies (Scruggs & Mastropieri, ; Scruggs et al., ). Students acquire academic vocabulary easily when student‐friendly definitions (i.e., using grade‐level‐appropriate vocabulary) are used rather than dictionary definitions (Beck et al., ).…”
Section: Effective Vocabulary Instruction In Social Studiesmentioning
confidence: 85%
“…Previous literature reviews (Scruggs & Mastropieri, ; Scruggs, Mastropieri, & Okolo, ) have identified the following causes of students’ low achievement in social studies. First, the social studies curriculum in elementary schools requires students to acquire both factual and conceptual knowledge (Korean Ministry of Education, ; National Council for the Social Studies [NCSS], ; Scruggs et al., ). However, factual and conceptual learning may be challenging for many students, because facts or concepts concerning social issues and events are often described using academic words in complex sentences (Beck, McKeown, & Kucan, ).…”
Section: Effective Vocabulary Instruction In Social Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the democratic process that guarantees all students, regardless of abilities, have the opportunities to receive a free and appropriate public education (Curtis, 1991;Ferretti, MacArthur, & Okolo, 2001). Yet, historically, students with SLD have received less history instruction than their peers without disabilities (Ferretti et al, 2001;Hughes & Parker-Katz, 2013;Scruggs, Mastropieri, & Okolo, 2008;Patton, Polloway, & Cronin, 1987;Schenning, Knight, & Spooner, 2013). Further complicating the issue is that o social studies often times receives less attention and priority in education than mathematics, science, or reading (Scruggs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, historically, students with SLD have received less history instruction than their peers without disabilities (Ferretti et al, 2001;Hughes & Parker-Katz, 2013;Scruggs, Mastropieri, & Okolo, 2008;Patton, Polloway, & Cronin, 1987;Schenning, Knight, & Spooner, 2013). Further complicating the issue is that o social studies often times receives less attention and priority in education than mathematics, science, or reading (Scruggs et al, 2008). Even when provided with the same history instruction as their peers without disabilities, students with SLD learn less content than their peers without disabilities and show fewer learning gains (Ferretti et al, 2001;Hughes & Parker-Katz, 2013).…”
Section: Introductionmentioning
confidence: 99%